Comparative analysis of clinical and instrumental study of the results of using standard and modified stromal-vascular fractions in the treatment of patients with chondromalacia patellae - G. M. Zverev; A. S. Sudnitsyn; S. V. Yakovlev; A. V. Saifulin; Sh. A. Moev (Genij Ortopedii, 2026)
Introduction Chondromalacia patellae is a leading cause of anterior knee pain and is considered an early form of degenerative patellofemoral cartilage disease. The limited regenerative potential of the hyaline cartilage and the variable effectiveness of conservative treatments motivate the search for biological technologies capable of providing structure-modifying effects. A promising approach is the use of autologous stromal vascular fraction (SVF) of adipose tissue that has anti-inflammatory and regenerative potential. The purpose of the work is to conduct a comparative assessment of clinical and instrumental studies of the results of standard and modified SVF therapy technologies in the treatment of patients with chondromalacia patella. Materials and Methods A non-randomized, retrospective, multicenter cohort study was performed. It included 41 patients with Outerbridge grades I–III chondromalacia patellae. Patients were divided into two groups according to treatment protocol provided: standard SVF (n = 20) and modified SVF (n = 21). Assessments were performed before treatment and after one, six, and 12 months. VAS, KOOS-PS, and quantitative parameters of cartilage defect based on MRI data (linear dimensions, area, volume) were analyzed. Differences were considered statistically significant at p < 0.05. Results In both groups, a significant reduction in pain and improvement in function were noted after 12 months (p < 0.001). In the standard SVF group, the defect area decreased by 27.4 % and volume by 44.6 %; in the modified SVF group, by 40.2 % and 53.8 %, respectively (p < 0.001). Intergroup comparison revealed a more pronounced decrease in defect width with the modified technique (p = 0.007). One month after treatment, the modified SVF group showed a more pronounced reduction in pain and improvement in function (p < 0.01), while the differences leveled out at six and 12 months. Discussion The modified SVF therapy technique resulted in earlier pain reduction and improved function compared to the standard technique. These differences leveled over the long term, confirming the high efficacy of SVF therapy regardless of the protocol variant. Comparable morphological results based on MRI data indicate that the structural effect was maintained with the modified technique. Limitations of the study include the non-randomized design and a moderate sample size. Conclusion SVF therapy demonstrates significant clinical and structural benefits in chondromalacia patellae. The modified technology provides a more rapid onset of clinical effect with comparable long-term morphological changes based on MRI data, suggesting it as a promising option for optimizing cell therapy.